Importancia de reformar el art. 424 del código orgánico de organización territorial, autonomía y descentralización (cootad), en lo concerniente al porcentaje destinado para áreas verdes en urbanizaciones y fraccionamientos urbanos - Morales Luzuriaga, Richar Vicente (2014)
The Organic Code of Territorial Organization, Autonomy and Decentralization (COOTAD), which I bring in validity as the Official Record Nro. 30 of Tuesday, the 19th of October 2010, in its art. 424 establishes that: in any organization and fractionation of the soil 10 % will be delivered to the municipality minimum and maximum 20 % calculated of the useful area of the urbanized or by installments area, as green and communal areas such goods of authority and public use will not be able to be changed of category inside the established status, will not be considered to the rims of gorge and its protection areas banks of the rivers and areas of protection, areas of risk, beaches and ecological areas of protection; every exoneration is prohibited to the contribution of green and communal areas except according to the current minimal lot as the territorial planning, in whose case will be compensated by the payment in money as the property avalúo. The Cantonal Decentralized Self-government, or called GADs Municipals, between its functions has of establishing the regime of use of the town-planning soil, for which it will determine the urban development conditions, parcelation, lotization, division or any other form of division (fractionation) in accordance with the cantonal planning, assuring percentages and communal green areas. This legal disposition, it grants a very wide margin so that the GAD, s policemen (policewomen) legislate in its respective ordinances on this topic; giving like result that if it is convenient(agrees) to the economic(economical) interests establishes the minimal of green areas; and that only few ones territorial districts really compromised with its fellow citizens and with the environment legislate with the maximum roof of the percentage dedicated to this end. Aware of the problem of the great cities of Europe and America, where its people have no minimum green areas; and, considering that our country is in the stage of creation and forming of large cities, are on time to avoid creating rules that eliminate difficult problems when cities expand. International organizations, including the World Health Organization (WHO) recommend minimum percentages of green areas, which should be made based on the inhabitants. In urban areas of Ecuador there are about 4.7 square meters (m2) of green space per citizen, a figure that does not reach the levels recommended by the World Health Organization (WHO) minimum. The study of this research, it is concluded that Ecuador should adopt regulations that prevent cities grow with this problem, the green areas into ecological aspect that is given to cities, these are for people in centers leisure, recreation and health.